RANCANG BANGUN MODEL MONITORING UNDERGROUND TANK SPBU DENGAN MENGGUNAKAN SENSOR ULTRASONIK BERBASIS INTERNET OF THINGS (IOT) - Sari, Sabrina Rianda; Halimatussa'diyah, RA; Zefi, Suzan; Duri, Rapiko (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
The management of underground tanks at gas stations is a crucial aspect to ensure the availability and safety of fuel. However, conventional methods for monitoring fuel levels in tanks are often ineffective and prone to human error. To address this issue, this research designs and develops a model for an underground tank monitoring system using ultrasonic sensors Internet of Things (IoT) integrated technology. The ultrasonic sensors are used to measure the fuel level in the tank in real-time, and this data is then transmitted to an IoT platform for analysis and monitoring through a user interface that can be accessed remotely. This system is expected to enhance operational efficiency and safety in the management of underground tanks at gas stations and provide early warnings in the event of abnormal conditions, such as leaks or excessively low fuel levels. The implementation results demonstrate that this system can provide accurate and reliable information, enabling better decision-making in fuel stock management